1977
DOI: 10.1128/iai.16.2.637-648.1977
|View full text |Cite
|
Sign up to set email alerts
|

Streptococcus mutans Dextransucrase: Functioning of Primer Dextran and Endogenous Dextranase in Water-Soluble and Water-Insoluble Glucan Synthesis

Abstract: The extracellular enzyme activities ofStreptococcus mutans 6715 that synthesize glucans from sucrose were concentrated and partially purified by ammonium sulfate precipitation and gel permeation column chromatography. Polyacrylamide gel analysis demonstrated that all of the major proteins precipitated by ammonium sulfate were quantitatively recovered in the high-molecularweight, enzyme-containing aggregates found in the void volume of the gel column. Anion-exchange column chromatography was used to fractionate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
52
0

Year Published

1978
1978
2018
2018

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 72 publications
(52 citation statements)
references
References 35 publications
0
52
0
Order By: Relevance
“…It has also been found that addition of glucan to extracellular GTase resulted in the formation of salt-stable enzyme-glucan complexes, indicating a high affinity of GTase for glucans (4-6). Germaine et al (5) have emphasized the roles of glucan and enzyme aggregation in enzyme binding to the cell surface. Furthermore, it is of interest to note that many "purified" GTase preparations contain a tightly bound carbohydrate (probably glucan) moiety (2,4,20).…”
Section: Resultsmentioning
confidence: 99%
“…It has also been found that addition of glucan to extracellular GTase resulted in the formation of salt-stable enzyme-glucan complexes, indicating a high affinity of GTase for glucans (4-6). Germaine et al (5) have emphasized the roles of glucan and enzyme aggregation in enzyme binding to the cell surface. Furthermore, it is of interest to note that many "purified" GTase preparations contain a tightly bound carbohydrate (probably glucan) moiety (2,4,20).…”
Section: Resultsmentioning
confidence: 99%
“…The necessity of a primer was first accepted in relation to glycogen synthesis mechanism studies carried out at the same period [43]. This hypothesis has been supported by the fact that addition of exogenous glucan has an activating effect on glucan synthesis [50, 52, 53]. However, glucansucrases are active enzymes in the absence of any exogenous primer.…”
Section: Mechanism Of Glucansucrase Actionmentioning
confidence: 99%
“…It was not established if the a-l-3 linkages were part of the main chains, or if two types of glucan synthesizing enzymes were present in S. mutans and $. sanguis, one synthesizing a-l-6-linked (soluble) and the other a-l-3-1inked (insoluble) polymer [46][47][48][49][50]. In the last 10 years knowledge of enzymes involved in mutan synthesis has increased and it is clear now that several glucosyltransferases are produced by mutans streptococci.…”
Section: Homopolysaccharidesmentioning
confidence: 99%